1980
DOI: 10.1172/jci109859
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Secreted Bacteroides Proteases on Human Intestinal Brush Border Hydrolases

Abstract: A B S T R A C T Selected bacteroides species secreted various amounts of protease and glycosidase into their growth medium. Bacteroides vulgatus, distasonis, and ovatus secreted the most (31-60% of total). The secreted protease was similar in action to the protease within the organism, in that it had a broad pH optimum of 6-9, a Km app. for casein of 0.1 ,uM, and was inhibited by benzamidine, phenylmethylsulfonyl fluoride, diisopropylfluorophosphate (DIFP), and by an elastase inhibitor, Ac(Ala)3AlaCH2Cl.Exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

1984
1984
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(37 citation statements)
references
References 33 publications
(41 reference statements)
1
35
0
1
Order By: Relevance
“…Both anaerobes and aerobes have been identified as responsible for the damage to the intestinal mucosa in SBS. Facultative anaerobes adhere to the epithelium and produce endotoxins, whereas aerobes produce enzymes (proteases) and other products that result in mucosal injury [16,34].…”
Section: Impact Of Sbbo On Gi Tract and Absorptionmentioning
confidence: 99%
“…Both anaerobes and aerobes have been identified as responsible for the damage to the intestinal mucosa in SBS. Facultative anaerobes adhere to the epithelium and produce endotoxins, whereas aerobes produce enzymes (proteases) and other products that result in mucosal injury [16,34].…”
Section: Impact Of Sbbo On Gi Tract and Absorptionmentioning
confidence: 99%
“…These findings suggest that duodenal and jejunal BBM-IAP released into the lumen during fat digestion might act within the lumen of the ileum and large intestine to detoxify LPS. IAP is relatively resistant to pancreatic proteases, consistent with the possibility that some IAP might survive transit to the colonic lumen in an active form (23).…”
Section: Discussionmentioning
confidence: 58%
“…B. fragilis has been shown to produce several proteases (Gibson & Macfarlane, 1988a, b) and some protease enzymes from this organism have been cloned and characterized (Van Tassel et al, 1992;Chen et al, 1995;Kling et al, 1997;Franco et al, 1997). It has been suggested that proteases play a role in the pathogenesis of this organism (Riepe et al, 1980;Moncrief et al, 1995) and it has also been demonstrated that the levels of protease production vary with the availability of ammonia (MacFarlane et al, 1993), with less protease activity being evident under excess ammonia conditions. The regulation of gdhB by organic nitrogen may be linked to protease activity and the breakdown of proteins in vivo, and hence to pathogenesis.…”
Section: Discussionmentioning
confidence: 99%